Clinical efficacy of launched JAK inhibitors in rheumatoid arthritis. (26th February 2019) - Taylor, Peter C
Abstract: Tofacitinib and baricitinib are the first orally available, small-molecule inhibitors of Janus kinase (JAK) enzymes to be approved for the treatment of RA. Tofacitinib is a selective JAK1, 3 inhibitor with less activity against JAK2 and TYK2 and baricitinib is a selective, oral JAK1, 2 inhibitor with moderate activity against TYK2 and significantly less activity against JAK3. Both drugs have undergone extensive phase III clinical trials in RA and demonstrated rapid improvements in disease activity, function and patient-reported outcomes as well as disease modification. Tofacitinib 5 mg bd, was approved by the Federal Drug Administration in 2012 for the treatment of RA in patients who are intolerant or unresponsive to MTX. An extended release formulation for the treatment of RA was approved by Federal Drug Administration in 2016. In 2017 the European Medicines Agency approved tofacitinib 5 mg bd in combination with MTX and baricitinib 4 mg and 2 mg once daily for the treatment of moderate to severe active RA in adult patients who are intolerant or unresponsive to one or more conventional synthetic DMARDs.